Pain evaluation in small animals – review - Ferreira, Luiz Fernando Lucas; Braccini, Paula; Franklin, Natália (Pubvet, 2015)
We studied all of the major scales for pain in small animals described in the literature. Observed the consensus of the need for training and clinical experience of the evaluators. The use of models that combine the assessment of physiological parameters with behavioral parameters, points to the best way to understand and assess a patient with pain.